'Sweet Dreams', 'Happy Days' and elevated 24-h urine 5-hydroxyindoleacetic acid excretion. (January 2013) - Hallin, Magnus Lars Peter; Mahmoud, Kamala; Viswanath, Ananth; Gama, Rousseau
We report two patients with markedly elevated 24-h urine 5-hydroxyindoleacetic acid (5-HIAA) excretion due to over-the-counter (OTC) self-medication with 5-hydroxytryptophan (5-HTP). It is important to recognize that OTC medication may cause increased 'false-positive' 5-HIAA excretion to prevent undue patient anxiety and unnecessary further investigation for carcinoid disease. Discordance between chromogranin A and 24-h urine 5-HIAA results should alert to the possibility of false-positive or -negative laboratory results.